Living Qur'an and Pencak Silat Culture: Practicing the Pager Wojo in Pagar Nusa UIN Saifuddin Zuhri Purwokerto - Mustofa, Aji; Kurniati, Listia; Alfikri, Fuad; Aisi, Muhamad Najih; Khusain, Moh Ali (UIN Maulana Malik Ibrahim Malang, 2025)
In the current digital age, there is a growing return to spiritual practices such as dhikr and Qur'anic recitation, which serve as sources of emotional resilience, moral grounding, and community cohesion within religious-based organizations like Pencak Silat Pagar Nusa. While studies on the integration of Islamic values in martial arts settings are growing, there remains a gap in understanding how specific Qur'anic verses, especially Ayat Kursi, are ritualized and pedagogically adapted in everyday spiritual practice. This study offers a novel contribution by examining the Pager Wojo ritual as a Living Qur'an phenomenon within Pagar Nusa at UIN Saifuddin Zuhri Purwokerto, focusing on the embodiment of Qur'anic teachings in localized martial traditions. Accordingly, this study aims to understand how the Qur'an, particularly Ayat Kursi, is interpreted, internalized, and practiced in daily life through protective rituals, reflecting a dynamic interaction between scripture and society. Employing qualitative field research methods and a Living Qur'an approach, this study utilizes Karl Mannheim’s sociology of knowledge to analyze the multifaceted meanings embedded in these ritual practices. Data were collected through observation, interviews, and documentation involving ritual participants. The findings reveal three layers of meaning: objective meaning, which frames the ritual as a medium for seeking divine protection and spiritual closeness; expressive meaning, which emphasizes its role in calming the heart and fostering a sense of safety; and documentary meaning, which highlights its function in Islamic da'wah and cultural preservation. The ritual incorporates specific breathing techniques combined with Qur'anic recitation, performed individually and collectively. This research concludes that the Pager Wojo ritual exemplifies how the Qur'an lives through communal practices, integrating Islamic teachings with local wisdom while preserving scriptural authenticity. Future research may consider comparative practices in other regions or adopt interdisciplinary approaches—such as psychology or health sciences—to assess the broader impact of embodied Qur'anic rituals on practitioners. Di era digital saat ini, terdapat peningkatan minat terhadap praktik spiritual seperti dzikir dan pembacaan Al-Qur'an sebagai sumber ketahanan emosional, landasan moral, dan kohesi sosial dalam organisasi berbasis agama seperti Pencak Silat Pagar Nusa. Penelitian ini mengkaji ritual Pager Wojo sebagai fenomena Living Qur'an di Pagar Nusa, UIN Saifuddin Zuhri Purwokerto, yang menunjukkan bagaimana ayat-ayat Al-Qur'an dihayati dan diwujudkan dalam tradisi seni bela diri lokal. Meskipun minat terhadap integrasi nilai-nilai Al-Qur'an dalam komunitas seni bela diri terus meningkat, studi-studi sebelumnya belum secara mendalam mengeksplorasi bagaimana ayat-ayat tertentu—seperti Ayat Kursi—diritualkan dalam praktik sehari-hari dan diadaptasi secara pedagogis dalam membentuk ekspresi spiritual. Oleh karena itu, studi ini bertujuan untuk memahami bagaimana Al-Qur'an, khususnya Ayat Kursi, ditafsirkan, diinternalisasi, dan dipraktikkan dalam kehidupan sehari-hari melalui ritual perlindungan, yang mencerminkan interaksi dinamis antara teks suci dan masyarakat. Dengan menggunakan metode penelitian lapangan kualitatif dan pendekatan Living Qur'an, studi ini menerapkan teori sosiologi pengetahuan dari Karl Mannheim untuk menganalisis makna berlapis dari praktik ritual tersebut. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dengan partisipan ritual. Temuan penelitian mengungkap tiga lapisan makna: makna objektif yang menunjukkan bahwa ritual ini menjadi sarana untuk mencari perlindungan ilahi dan kedekatan spiritual; makna ekspresif yang menyoroti fungsi ritual sebagai praktik penenang hati dan perlindungan diri; serta makna dokumenter yang menggambarkan perannya dalam dakwah Islam dan pelestarian budaya. Ritual ini melibatkan teknik pernapasan khusus yang dikombinasikan dengan pembacaan ayat-ayat Al-Qur'an, dilakukan secara individu maupun kolektif. Penelitian ini menyimpulkan bahwa ritual Pager Wojo merupakan contoh nyata bagaimana Al-Qur'an hidup dalam praktik komunitas, dengan berhasil mengintegrasikan ajaran Islam dan kearifan lokal tanpa mengabaikan keaslian teks suci. Penelitian selanjutnya dapat mengeksplorasi praktik serupa di wilayah lain atau menggabungkan pendekatan interdisipliner, termasuk psikologi atau ilmu kesehatan, untuk menilai dampak yang lebih luas dari ritual Al-Qur'an yang diwujudkan secara fisik bagi para praktisinya.